Profiling of Brevetoxin Metabolites Produced by Karenia brevis 165 Based on Liquid Chromatography-Mass Spectrometry - Shen, Huihui; Song, Xiuxian; Zhang, Yue; Zhang, Peipei; Li, Jing; Song, Weijia; Yu, Zhiming (Toxins, 2021)
In this study, Karenia brevis 165 (K. brevis 165), a Chinese strain, was used to research brevetoxin (BTX) metabolites. The sample pretreatment method for the enrichment of BTX metabolites in an algal culture medium was improved here. The method for screening and identifying intracellular and extracellular BTX metabolites was established based on liquid chromatography-time-of-flight mass spectrometry (LC-ToF-MS) and liquid chromatography triple quadrupole tandem mass spectrometry (LC-QqQ-MS/MS). The results show that the recovery rates for BTX toxins enriched by a hydrophilic–lipophilic balance (HLB) extraction column were higher than those with a C18 extraction column. This method was used to analyze the profiles of extracellular and intracellular BTX metabolites at different growth stages of K. brevis 165. This is the first time a Chinese strain of K. brevis has been reported that can produce toxic BTX metabolites. Five and eight kinds of BTX toxin metabolites were detected in the cell and culture media of K. brevis 165, respectively. Brevenal, a toxic BTX metabolite antagonist, was found for the first time in the culture media. The toxic BTX metabolites and brevenal in the K. brevis 165 cell and culture media were found to be fully proven in terms of the necessity of establishing a method for screening and identifying toxic BTX metabolites. The results found by qualitatively and quantitatively analyzing BTX metabolites produced by K. brevis 165 at different growth stages show that the total toxic BTX metabolite contents in single cells ranged between 6.78 and 21.53 pg/cell, and the total toxin concentration in culture media ranged between 10.27 and 449.11 μg/L. There were significant differences in the types and contents of toxic BTX metabolites with varying growth stages. Therefore, when harmful algal blooms occur, the accurate determination of BTX metabolite types and concentrations will be helpful to assess the ecological disaster risk in order to avoid hazards and provide appropriate disaster warnings.